2003
DOI: 10.1002/ajim.10277
|View full text |Cite
|
Sign up to set email alerts
|

Work organization and patient care staff injuries: The impact of different care models for “alternate level of care” patients

Abstract: The way in which ALC care is organized in hospitals affects the risk and severity of injuries among patient care staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…These units also feature staff reorganization where acute nursing is reduced and personal supports as well as allied health professionals are increased. Such units are have been found to reduce staff injury [56,57]. Likewise, the use of rehabilitation has been shown to reduce delayed discharge rates [58].…”
Section: Discussionmentioning
confidence: 99%
“…These units also feature staff reorganization where acute nursing is reduced and personal supports as well as allied health professionals are increased. Such units are have been found to reduce staff injury [56,57]. Likewise, the use of rehabilitation has been shown to reduce delayed discharge rates [58].…”
Section: Discussionmentioning
confidence: 99%
“…Fuortes et al (1994)14 found the incidence of low-back injury in CAs was 3.3 times higher than in RNs and LPNs. Ostry et al (2003)36 found that in acute care, LPNs aggregated with CAs were more likely than RNs to experience: any injury (1.59 times), patient-care injury (1.80 times) and violence-related injury (3.25 times). The different tasks between occupations may explain injury differences between occupations and these differences agree with the findings from previous studies using facility-specific data (e.g., Ostry et al ) 36.…”
Section: Discussionmentioning
confidence: 99%
“…Ostry et al (2003)36 found that in acute care, LPNs aggregated with CAs were more likely than RNs to experience: any injury (1.59 times), patient-care injury (1.80 times) and violence-related injury (3.25 times). The different tasks between occupations may explain injury differences between occupations and these differences agree with the findings from previous studies using facility-specific data (e.g., Ostry et al ) 36. However, as suggested above, facility-specific data produce higher injury rates than rates reported by Workers Compensation Boards, as the generic denominator data used by Compensation Boards tend to result in lower injury estimates than the actual exposure risk.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that violence-related injuries and musculoskeletal disorders are more common in direct care workers compared to other health care professionals (Fredriksson et al, 2002; Fuortes, Shi, Zhang, Zwerling, & Schootman, 1994; Ostry et al, 2003). Research has also shown that direct care workers have less control over their work environment, fewer opportunities to make independent decisions, and higher levels of job strain than other occupational groups (Morgan, Semchuck, Stewart, & D’Arcy, 2002; Sullivan, Kerr, & Ibrahim, 1999).…”
Section: Discussionmentioning
confidence: 99%